Pengembangan Media Pembelajaran Google Sites untuk Meningkatkan Hasil Belajar IPAS tentang Keanekaragaman Hayati bagi Siswa Kelas IV di SD Negeri 2 Binorong - Shabhira, Helmita Hana; Astuti, Tri (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2026)
Learning biodiversity content in IPAS subjects at the elementary school level still encounters several challenges, particularly low student interest and learning achievement caused by the limited utilization of digital learning media. This research was conducted to design and assess the practicality and impact of Google Sites–based learning media for teaching biodiversity to fourth-grade students. The research utilizes a Research and Development approach based on the ADDIE framework, which includes the stages of analysis, design, development, implementation, and evaluation. The participants consisted of 23 fourth-grade students at SD Negeri 2 Binorong. Data were obtained through observations, questionnaires, and pretest–posttest instruments. The findings revealed that the developed Google Sites–based learning media was classified as highly feasible, with validation results of 98.33% from material experts and 93.33% from media experts. The paired t-test showed significant pretest–posttest differences, and N-Gain analysis indicated moderate to high learning gains, confirming the feasibility and effectiveness of Google Sites–based media for elementary IPAS instruction.